Two Steps in One Pot: Enzyme Cascade for the Synthesis of Nor(pseudo)ephedrine from Inexpensive Starting Materials1. Issue 26 (9th May 2013) - Sehl, Torsten; Hailes, Helen C.; Ward, John M.; Wardenga, Rainer; von Lieres, Eric; Offermann, Heike; Westphal, Robert; Pohl, Martina; Rother, Dörte
<x xml:space="preserve">Abstract</x> Two steps in one pot: An enzyme cascade consisting of a lyase and an (R)‐ or (S)‐selective ω‐transaminase (TA) provides (1R, 2R)‐norpseudoephedrine and (1R, 2S)‐norephedrine in only two steps. The intermediate is not isolated in this one‐pot reaction and the products are obtained in high enantio‐ and diastereomeric purity. Moreover, the by‐product from the second reaction can be recycled to serve as the substrate for the first reaction.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>